2016
DOI: 10.1038/srep28143
|View full text |Cite
|
Sign up to set email alerts
|

Salivary total α-synuclein, oligomeric α-synuclein and SNCA variants in Parkinson’s disease patients

Abstract: The present study was to evaluate the diagnostic value of salivary total and oligomeric α-synuclein levels in PD. Furthermore, we sought to explore the relationship between salivary total α-synuclein and α-synuclein SNP variants levels. 201 PD patients and 67 controls were recruited, of which there also had the genetic information of two positive α-synuclein (SNCA) loci. Salivary total α-synuclein was assayed using a highly sensitive Luminex assay and oligomeric α-synuclein was quantified by the combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 31 publications
5
70
4
2
Order By: Relevance
“…Yet, both increases and decreases in salivary total a-syn have been reported [72][73][74]. On the other hand, increases in oligomeric asyn [75] and oligomeric a-syn/total a-syn ratio have been demonstrated to be specific for PD [74,76]. To date, there has been no investigation of salivary a-syn in AD.…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Yet, both increases and decreases in salivary total a-syn have been reported [72][73][74]. On the other hand, increases in oligomeric asyn [75] and oligomeric a-syn/total a-syn ratio have been demonstrated to be specific for PD [74,76]. To date, there has been no investigation of salivary a-syn in AD.…”
Section: Alpha-synucleinmentioning
confidence: 99%
“…Saliva has advantages over other biofluids and imaging techniques because its acquisition is noninvasive, inexpensive, and requires minimal personnel training . Most groups report reduced salivary total α‐synuclein levels and higher oligomeric α‐synuclein levels in PD patients when compared with controls in addition to higher oligomeric to total α‐synuclein ratios …”
mentioning
confidence: 99%
“…10,11 Most groups report reduced salivary total α-synuclein levels and higher oligomeric α-synuclein levels in PD patients when compared with controls in addition to higher oligomeric to total α-synuclein ratios. [12][13][14][15][16] In 2018, we reported increased concentrations of salivary heme oxygenase-1 (HO-1) in early-stage PD patients when compared with non-neurological controls. 17 HO-1 catalyzes the degradation of heme to biliverdin (further catabolized to bilirubin), free ferrous iron, and carbon monoxide.…”
mentioning
confidence: 99%
“…However, these differences did not reach statistical significance, suggesting that t-a-syn would not suffice as a single biomarker in saliva. Other studies have focused on evaluating o-a-syn, reporting a marked increase in PD patients compared to healthy controls (Kang et al 2016), suggesting that the oligomeric form may have a greater potential for a disease biomarker (Kang et al 2016;Vivacqua et al 2016;Vivacqua et al 2019). This was further supported when o-asyn was evaluated in PD patients at different Hoehn & Yahr (H&Y) stages of the disease and reported significant increases with advancing disease stages.…”
Section: Levels Of Salivary A-synmentioning
confidence: 89%
“…Besides blood and CSF, α‐syn has also been explored to a lesser extent in other biofluids, such as saliva. Two studies reported reduced levels of saliva t‐α‐syn in PD compared to healthy controls (Devic et al ; Kang et al ), as well as lower levels of saliva t‐α‐syn in older patients (Kang et al 2016) . However, these differences did not reach statistical significance, suggesting that t‐a‐syn would not suffice as a single biomarker in saliva.…”
Section: Levels Of Salivary α‐Synmentioning
confidence: 99%